Knowledge management as a strategic tool in organization performance: a review of literature - Mohd Sadad, Mahmud; Nik Hazimi, Mohammed Foziah; Yusnita, Yusof (2020)
Knowledge management is a very valuable lever for business, knowledge is main strategic stock within organization specially that knowledge which is available as a competitiveness for an enterprise. This research bring out the knowledge management as a strategic tool in organization to gain the competitive advantage in a marketplace. Researchers concluded that the good management of knowledge clears an organization ability to bring the innovation rather than managing with the change which has been happen in business society. Efficient knowledge management is very important for an organization. Moreover, knowledge management is a very important functional for the firms specially business organizations.